139: Breastfeeding Knowledge, Confidence, Beliefs and Attitudes of Canadian Physicians. Issue 6 (1st June 2014) - Pound, C; Williams, K; Grenon, R; Aglipay, M; Plint, AC
Abstract: BACKGROUND: Physicians' attitudes and recommendations directly impact breastfeeding duration. Yet, studies in other parts of the world have shown that physicians lack the skills to offer proper guidance to breastfeeding mothers. OBJECTIVES: This study aims to identify gaps in breastfeeding knowledge, confidence, beliefs and attitudes of Canadian physicians, and factors associated with breastfeeding knowledge. DESIGN/METHODS: A breastfeeding questionnaire was developed and piloted for validity. These questionnaires were sent to 1429 pediatricians (PED) and 1329 family physicians (FP), for a target sample size of 385 per group, and to final-year pediatric and family medicine residents (PR and FMR). Multiple linear regression was used to identify factors independently associated with knowledge score. RESULTS: The analysis included 397 PED, 322 FP, 17 PR and 44 FMR who completed the questionnaire. Mean overall correct knowledge score was 67.8% for PED, 64.3% for FP, 72.7% for PR and 66.8% for FMR. 285 PED (74.2%), 228 FP (73.1%), seven PR (41.2%) and 21 FMR (53.8%) felt confident with their breastfeeding counseling skills, but few PED and FP (5.1% and 11.3%) routinely observed breastfeeding in mother-infant pairs. Most participants (72.1%) felt that residency had prepared them poorly or somewhat poorly to support breastfeeding mothers. Independent predictors of breastfeeding knowledge included female gender, >50% of one's practice under one year of age, breastfeeding one's own child, self-directed learning and confidence teaching mothers about breastfeeding. CONCLUSIONS: Breastfeeding knowledge, confidence, beliefs and attitudes are suboptimal among Canadian physicians. Confidence and knowledge are closely intertwined, and currently develop through learning methods other than residency training. This study identified specific areas of concerns in physicians' breastfeeding knowledge, confidence, beliefs and attitudes, allowing for the development of targeted educational tools that will help physicians better support breastfeeding.